Don't be a stranger : Russian literature and the perils of not fitting in - Galie, Jason, 1973- (Academic Studies Press, 2022)
"It is human nature to want to fit in. The lengths people have gone to do so have provided creative minds with material for centuries. This book explores the consequences of being marked an outsider in the Russian-speaking world through a close study of several seminal works of Russian literature. The author combines the fields of literary studies, linguistics, and sociology to illuminate what prompted Christof Ruhl, an economist at the World Bank, to comment, about Russia, "On a very broad scale, it's a country where people care about their family and friends. Their clan. But not their society.""--